REKONSTRUKSI KONSEP NAFKAH DALAM HUKUM KELUARGA ISLAM: PERSPEKTIF GENDER DAN OTONOMI PEREMPUAN - Hardianti; Nurchaliq Majid (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This research examines the concept of nafkah and women's autonomy from gender and Islamic family law perspectives by investigating the dynamics of nafkah interpretation and its implications for women's independence in Muslim families. Using qualitative research methods with a literature study approach, this research analyzes the thoughts of classical and contemporary scholars, especially Murtaḍhā Muṭhahhari and Faqihuddin Abdul Kodir, and contextualizes them with the social reality of Indonesian Muslim society. The results show that traditional interpretations of nafkah tend to limit women's autonomy through the construction of economic dependency, while contemporary approaches offer a more inclusive understanding that accommodates women's financial independence. Contextualization of the nafkah concept through the principle of "mubādalah" (reciprocity) proves to be more aligned with the objectives of sharia in realizing justice and benefit, while opening space for women's autonomy without negating shared responsibility in building a sakinah family. This research contributes to the development of gender-responsive Islamic family law that accommodates social change without abandoning principles.